2017
DOI: 10.1038/s41598-017-13636-1
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic selenium and its hepatoprotective activity

Abstract: Elemental selenium nanoparticles (SeNPs) have multiple biological activities. In this study, we investigated the protective effects of biogenic SeNPs (BioSeNPs) on CCl4-induced liver damage in mice. The results showed that: (i) when compared to sodium selenite (SS), BioSeNPs has a similar tissue distribution after intragastrical administration to mice; (ii) BioSeNPs and SS showed comparable efficacy in increasing the activities of glutathione peroxidase and thioredoxin reductase in liver cell lines, mice blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
3
13
0
Order By: Relevance
“…As presented in Figure 6, the serum and hepatic Se levels in the Se-supplementation groups were significantly higher than those of other groups (p < 0.05), indicating that CS-SeNPs might enhance the Se stock in the animals. This is in line with the reported efficient Se-retention capacity of some SeNPs stabilized by other macro-molecules [2,3,25,40] or microorganisms [17], confirming the potential of nanoparticles in Se supplementation. Se retention by extra Se supplementation needs to be discussed.…”
Section: Se Retentionsupporting
confidence: 88%
See 1 more Smart Citation
“…As presented in Figure 6, the serum and hepatic Se levels in the Se-supplementation groups were significantly higher than those of other groups (p < 0.05), indicating that CS-SeNPs might enhance the Se stock in the animals. This is in line with the reported efficient Se-retention capacity of some SeNPs stabilized by other macro-molecules [2,3,25,40] or microorganisms [17], confirming the potential of nanoparticles in Se supplementation. Se retention by extra Se supplementation needs to be discussed.…”
Section: Se Retentionsupporting
confidence: 88%
“…The third point is the broad hepatoprotection of SeNPs. It was reported that SeNPs alone or combined with vitamins might protect animals from the hepatic injury caused by toxic chemicals (e.g, carbon tetrachloride [17], acetaminophen [18], and acrylamide [19]) or by pathogen infections (e.g, Schistosoma spp. [20]).…”
Section: Groupmentioning
confidence: 99%
“…In our study, toxic effects on liver tissue at the biochemical level were not observed. Similar results were reported by Li et al [35]. Compared to sodium selenite, biogenic SeNPs showed a protective effect on liver parenchyma and inhibiting effect for the elevation of the level of liver enzymes in carbon tetrachloride-induced liver damage in mice.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, rats co-treated with Sel demonstrably ameliorate DCF-induced hepatic injury dose-dependently, evaluated by transaminases levels in serum. 48,49 Renal function marker enzymes such as urea and creatinine are metabolic waste products primarily excreted in the urine. They are important in the diagnosis of kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, rats co-treated with Sel demonstrably ameliorate DCF-induced hepatic injury dose-dependently, evaluated by transaminases levels in serum. 48,49…”
Section: Discussionmentioning
confidence: 99%